Bubuia: um jogo educacional para reforçar o aprendizado da matemática do ensino fundamental I - Lima, Djavan Ferreira (Brasil, 2019)
In the current scenario, society makes constant use of information and communication technologies, thereby expanding teaching methods of teaching and learning through its various devices, software and media currently available to provide students with active learning. On the other hand, the mathematical discipline is considered difficult to learn because it contains complex data resulting in a low learning rate according to each student profile. In this context, this work aims to develop a digital educational game, called Bubuia, to reinforce the learning of mathematical content related to elementary school I. The methodology consists of a bibliographic survey to support the initial proposal, therefore the construction of software with based on the specification of requirements. After that, the usability evaluation of the game was performed by applying a questionnaire with teachers and students of elementary school, based on the System Usability Scale system. In the evaluation with the participants of the teacher profile it was observed that the game obtained a high level of agreement in the questions that refer to the ease of use, learning and satisfaction. In the student profile was obtained the total average with the value of 78.6 according to the evaluation criteria of the method used, which represents a good index of satisfaction with the game developed.